Pengadaan Bidak Baca untuk Memperkuat Kemampuan Literasi Siswa SD Inpres 138 Matawolot - Adi Iwan Hermawan; Abdul Hafid; Rima Rima; Siti Fatihaturrahmah Al Jumroh; Kartika Tiara Syarifuddin; Selfiani Selfiani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity aims to improve elementary school students' literacy skills through the provision of innovative learning media, "Bidak Baca," at SD Inpres 138 Matawolot. This program is motivated by the low interest in reading and basic literacy skills among lower-grade students, which is further exacerbated by the lack of engaging and relevant learning media for their lives. To achieve this goal, the implementation method of this activity uses a participatory approach that involves several stages, namely needs observation, planning, media production, teacher training, and evaluation of the use of the provided media. The results of this activity indicate that the Bidak Baca media successfully increased student motivation and participation in reading activities. This media not only functions as an aid, but also helps teachers in creating a fun, active, and educational game-based literacy learning atmosphere. With this media, students not only learn to recognize letters and words, but also begin to build confidence in reading and discussing with their friends. In conclusion, the provision of Bidak Baca media is an effective and simple strategy to encourage the growth of a culture of literacy from an early age in elementary schools. Furthermore, this method can be easily replicated in other educational institutions, thus hopefully having a broader positive impact on improving literacy among students in various regions. Thus, this effort is expected to contribute to improving the quality of education in Indonesia and creating a smarter and more competitive generation in the future. Through this activity, it is hoped that students will develop a greater love of reading and make literacy an essential part of their daily lives.